2012
DOI: 10.1016/j.drugpo.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption patterns and sexual risk behavior among female sex workers in two South Indian communities

Abstract: Background HIV transmission in India is primarily heterosexual and there is a concentrated HIV epidemic among female sex workers (FSWs). Earlier reports demonstrate that many FSWs consume alcohol regularly before sexual encounters. This qualitative study is part of a larger quantitative study designed to assess alcohol consumption patterns among female sex workers and their association with sexual risk taking. Here we investigate the environmental influence, reasons for and consequences of consuming alcohol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…The quantitative survey reported in this paper applied a cross-sectional design and was conducted among 1,139 female sex workers in Chirala, Andhra Pradesh (n=589) and Calicut, Kerala (n=550) in South India during 2009 and 2010. Detailed descriptions of the study sites and the original research study can be found elsewhere (Rodriguez et al 2010; Heravian et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The quantitative survey reported in this paper applied a cross-sectional design and was conducted among 1,139 female sex workers in Chirala, Andhra Pradesh (n=589) and Calicut, Kerala (n=550) in South India during 2009 and 2010. Detailed descriptions of the study sites and the original research study can be found elsewhere (Rodriguez et al 2010; Heravian et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Findings also indicates that alcohols using female sex workers are extremely less likely to use a condom most of the time; irrespective of the type of sexual partner. These findings suggest that alcohol using female sex workers need to be targeted by the prevention programs with better exigency to make the HIV and STI prevention programs more successful [24][25][26].…”
Section: Discussionmentioning
confidence: 97%
“…Alcohol consumption may contribute to sexual risk taking and ultimately the spread of HIV [6][7][8]. Studies from other countries document associations between alcohol use and high-risk heterosexual behaviours among those with and without HIV infection [9]. In India HIV transmission is primarily heterosexual and there is a concentrated HIV epidemic among female sex workers (FSWs) [10].…”
Section: Journal Of Infectious Diseases and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported alcohol use as a risk factor for inconsistent condom use (Heravian et al, 2012; Li, Li, & Stanton, 2010). This study also provides evidence to support similar findings.…”
Section: Discussionmentioning
confidence: 99%